2018
DOI: 10.1111/add.14402
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and all‐cause mortality in older adults in Spain: an analysis accounting for the main methodological issues

Abstract: After accounting for potential biases, light-to-moderate drinking among people 60+ years of age appears to have no statistically significant benefit on mortality compared with abstention from alcohol. By contrast, heavy/binge drinking shows a higher death risk compared with abstention from alcohol. Alcohol intake appears to have a positive dose-response with mortality among drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 43 publications
5
37
0
Order By: Relevance
“…While previous studies found that smoking was a risk factor for all-cause mortality [11], our results found no statistically signi cant difference, which is possibly explained by the quitter bias (people may stop smoking because they are in poor health and may be advised not to continue). The results of the risk study on alcohol consumption were basically consistent with the results of Ortolá et al, which showed that there was no statistically signi cant difference in mortality between light-to-moderate alcohol consumption and no alcohol consumption among people over 60 years old [34]. As well, we found the greater all-cause mortality risk among persons with underweight (BMI < 18.5 kg/m 2 ) in this study, which agreed with previous studies [21,35,36].…”
Section: Discussionsupporting
confidence: 89%
“…While previous studies found that smoking was a risk factor for all-cause mortality [11], our results found no statistically signi cant difference, which is possibly explained by the quitter bias (people may stop smoking because they are in poor health and may be advised not to continue). The results of the risk study on alcohol consumption were basically consistent with the results of Ortolá et al, which showed that there was no statistically signi cant difference in mortality between light-to-moderate alcohol consumption and no alcohol consumption among people over 60 years old [34]. As well, we found the greater all-cause mortality risk among persons with underweight (BMI < 18.5 kg/m 2 ) in this study, which agreed with previous studies [21,35,36].…”
Section: Discussionsupporting
confidence: 89%
“…While numerous studies have examined the relationship between alcohol consumption and mortality, methodological limitations have abounded. In a recent meta‐analysis (Stockwell et al., ), Stockwell and colleagues noted that of 87 studies, at least 65 used a reference group of abstainers that included former drinkers, suggesting the potential for selection bias (Licaj et al., ; Ortolá et al., ). Similar biases were highlighted in an additional meta‐analysis examining alcohol consumption and cardiovascular disease (Zhao et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to abstainers and heavy drinkers, moderate drinkers are wealthier and present more protective factors for cardiometabolic health (Cerdá et al., ; Dawson et al., ; French et al., ; Lang et al., ; Naimi et al., ; Rehm et al., ; Skog, ), and many studies do not have comprehensive information sufficient for confounder control. Further, the extent to which associations arise because of reverse causation (individuals reducing consumption due to illness) remains a threat to validity (Licaj et al., ; Ortolá et al., ; Stockwell et al., ). An instrumental variable approach like Mendelian randomization, which does not rely on standard confounder control, demonstrates little evidence for a protective effect of moderate consumption on cardiovascular disease (Cho et al., ; Holmes et al., ; Millwood et al., ; Taylor et al., ).…”
mentioning
confidence: 99%
“…All patients with a history of EH, ranging from 3 months to 47 years, had normal-range blood pressure as they were on antihypertensive medication. As against the personal history of subjects, there was a very significant improvement in habits of smoking (≥5 cigarettes each day [26] ), alcohol consumption (≥140 g per week [27] ), and physical activity (>30 min of aerobic exercise ≥2 times per week [28] ) after post-diagnosis professional education in the EH group. All subjects in this study were of Han ethnicity.…”
Section: Methodsmentioning
confidence: 99%